EVALUATING ISLAMIC EDUCATION PROGRAMS: A CONCEPTUAL AND NARRATIVE REVIEW OF PRINCIPLES, FRAMEWORKS, AND IMPLEMENTATION - Agung Fahri; Salsabila Shafha Firabiawwalia; Sovia Masayu; Deti Elice (STKIP Pesisir Selatan, 2025)
Islamic education programs operate within complex educational environments that demand both measurable accountability and the preservation of Islamic moral spiritual values, creating distinctive challenges for program evaluation. This study aims to critically synthesize and conceptualize scholarly perspectives on the evaluation of Islamic education programs by examining their underlying principles, dominant frameworks, and implementation practices. Employing a conceptual and narrative literature review design, relevant studies published between 2018 and 2025 in internationally indexed and nationally accredited journals were purposively selected and thematically analyzed to identify convergent and divergent patterns. The findings reveal that evaluation practices in Islamic education remain largely dominated by outcome-based and accountability-driven models, often driven by external quality assurance and accreditation requirements, which inadequately represent holistic educational aims such as ethical formation and spiritual development. At the same time, the literature consistently emphasizes value-based evaluation principles grounded in Islamic educational philosophy, including holistic human development, moral accountability, and maqāṣid al-sharīʿah, yet these principles are rarely operationalized within coherent evaluative frameworks.